Desarrollos didácticos del Archivo del Patrimonio Inmaterial de Navarra (APIN): un proyecto de Lengua castellana y Literatura en Secundaria - López Pérez, Mª Victoria (Huarte de San Juan. Filología y Didáctica de la Lengua, 2016)
This work presents a didactic experience which was put into practice during a 3rd year Secondary Education Spanish Language and Literature course. It was based on the Digital Archive of the Immaterial Heritage of Navarra (APIN), whose educational potential in the different curricular areas is yet to be explored. The experience consisted in the implementation of a project entitled «Yesterday’s and Today’s pastimes », which included a final task of recording interviews about their free time activities to informants from different generations from a small town in Navarre. These recordings will eventually be included among the Spanish audio-visual testimonies of the APIN in one of its domains, the one related to the collective sociability practices. 25 students from a public secondary school participated in the project, during the academic year 2014-15; it was carried out in three phases and it included the following learning outcomes: development of the linguistic competence (the interview and the features of ethnolinguistic vitality), of the cultural competence (familiarization with the APIN) and of the digital competence.
Keywords: Project-based leaning; linguistic competence; cultural competence; digital competence; compulsory Secondary Education